(3GdJNWjW GdYdej gh WQjb GdZOs - (3CHh GdfLG, GdSjOs ((3GdbGgQI (B:s (3GdeQcR GdYQHj ddHMhK hGdEOGQI,s, 1967)
(3bQGQ QFjS GdLeghQjI GdYQHjI GdeJMOI Qbe (B1329 (3dSfI (B1960 (3aj TCf EYOGO GdNWI GdYGeI ddOhdI heJGHYI JfajPgG(B.s
Keywords: (3GdEOGQI GdYGeIs -- (3JWhjQs -- (3eUQs